Minimized thermal expansion mismatch of cobalt-based perovskite air electrodes for solid oxide cells. Issue 47 (30th November 2021) - Li, Zhishan; Peng, Meilan; Zhao, Yingru; Li, Jianhui; Sun, Yifei
Abstract : The as-obtained R-BZCY-Co x air electrode shows a 7-fold enhancement in electrochemical performance with a negligible TEC mismatch of only ∼11.4%. Abstract : The mismatch of thermal expansion coefficients (TECs) between cobalt-containing perovskite air electrodes and electrolytes is a great challenge for the development of thermo-mechanically durable solid oxide cells (SOCs). In this work, we propose a facile design principle to directly grow highly dispersed Co reactive sites onto ion-conducting scaffolds and confine the dimension of active centres within nanoscale. As a representative, the Co-socketed BaCe0.7 Zr0.2 Y0.1 O3− δ perovskite (denoted as R-BCZY-Co) was constructed via a consecutive sol–gel and in situ exsolution approach. Combined XRD, H2 -TPR, SEM and TEM results confirm the emergence of Co nanoparticles on a BCZY matrix without the segregation of a secondary Co-rich phase. The symmetric half-cell measurement suggests that R-BCZY-Co air electrode with the optimal Co content of 10 mol% exhibits a 7-fold promoted oxygen activation performance with a polarization resistance of ∼0.17 Ω cm 2 at 750 °C. The TEC mismatch between fabricated R-BCZY-Co electrodes and BCZY electrolytes is minimized down to only ∼11.4%, which is significantly lower than that of other representative counterparts. Moreover, the detailed XPS result proves that the architecture of exsolved Co on BCZY possesses a higher concentration of surface oxygen vacancy, which further benefits the kinetics of ion diffusion and oxygen absorption.